Literasi Digital, Keamanan Digital, dan Komunikasi Digital terhadap Pencegahan Cyberbullying pada Generasi Z di Platform Tiktok - Stefanus Eko Prasetyo; Tony Wibowo; Melisa Melisa (Jurnal Penelitian Teknologi Informasi dan Sains, 2026)
The proliferation of social media interactions frequently results in an increased risk of cyberbullying. This study aims to evaluate the impact of digital literacy, digital security, and digital communication on cyberbullying prevention among Generation Z TikTok users. Employing an explanatory quantitative approach, data were collected through online questionnaires distributed to Generation Z students in the Information Systems Study Program at Universitas Internasional Batam. The respondent data were then analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique. The analytical results reveal that digital literacy does not significantly affect cyberbullying prevention. Conversely, both digital security and digital communication demonstrate a significant impact on cyberbullying prevention. Among the investigated variables, digital communication exerts the most dominant influence on preventing cyberbullying. These findings suggest that preventing cyberbullying requires more than merely digital knowledge; it heavily relies on the implementation of digital security measures and the capacity for ethical communication in digital environments. Ultimately, this research is expected to serve as a valuable reference for formulating effective cyberbullying mitigation strategies for Generation Z across social media platforms.